Journey to the centre of the cell: Virtual reality immersion into scientific data. (21st November 2017) - Johnston, Angus P.R.; Rae, James; Ariotti, Nicholas; Bailey, Benjamin; Lilja, Andrew; Webb, Robyn; Ferguson, Charles; Maher, Sheryl; Davis, Thomas P.; Webb, Richard I.; McGhee, John; Parton, Robert G.
Abstract : Visualization of scientific data is crucial not only for scientific discovery but also to communicate science and medicine to both experts and a general audience. Until recently, we have been limited to visualizing the three‐dimensional (3D) world of biology in 2 dimensions. Renderings of 3D cells are still traditionally displayed using two‐dimensional (2D) media, such as on a computer screen or paper. However, the advent of consumer grade virtual reality (VR) headsets such as Oculus Rift and HTC Vive means it is now possible to visualize and interact with scientific data in a 3D virtual world. In addition, new microscopic methods provide an unprecedented opportunity to obtain new 3D data sets. In this perspective article, we highlight how we have used cutting edge imaging techniques to build a 3D virtual model of a cell from serial block‐face scanning electron microscope (SBEM) imaging data. This model allows scientists, students and members of the public to explore and interact with a "real" cell. Early testing of this immersive environment indicates a significant improvement in students' understanding of cellular processes and points to a new future of learning and public engagement. In addition, we speculate that VR can become a new tool for researchers studying cellular architecture and processes by populating VR models with molecular data. Abstract : Visualization of microscopy data using virtual reality headsets has the potential to transform the way we understand, interact with and teach cell biology. In this study, we show how serial block‐face SEM data can be used to build a three‐dimensional (3D) virtual model of a cell that allows scientists, students and members of the public to explore and interact with a "real" cell.